The Effect of Black Cumin Seed (Nigella sativa l.) Extract to Alloxan Induces Pancreatic Tissue Catalase Enzyme Activity of Male Wistar Rats (Rattus norvegicus) - Qonita Achmad; Irmawati Dikman; Sulistiana Prabowo (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2018)
Alloxan causes the formation of reactive oxygen through the reduction process of alloxan (dialuric acid) in the β cells of pancreas. Free radicals cause damage  and decrease catalase enzyme activity. Black cumin seeds extract which contain carotenoids, thymoquinone, carvacrol, 4-terpineol, t-anethole, and tert-butylhydroquinone (TBHQ) has antioxidant activity that is expected to inhibit reactive oxygen species (ROS) that is expected to increase pancreatic catalase activity. This study used 24 male Wistar rats, divided into 3 groups:1)group of rats fed with standard food, 2)group of rats induced by alloxan 125mg/kg /BB intraperitoneally on day 1, 3)groups of rats induced by alloxan 125mg/kg/BB intraperitoneally on day 1 and were given by black cumin seed extract 2500mg/kg/BB orally on day 4 until 17. On the 18th day of all rats were sacrificed and pancreatic tissue catalase activity were measured by the spectrophotometric method. The results of One-Way ANOVA showed significant difference (p=0.003) pancreatic tissue catalase activity of groups of rats fed with standard food (1696,96U/g±414,10U/g) compared with group of rats induced by alloxan (1287,58U/g±88,45U/g). There was significant difference (p=0.001) of pancreatic tissue catalase activity of groups of rats induced by alloxan (1287,58U/g±88,45U/g) with a group of rats induced by alloxan and given with black cumin seed extract (1764,83U/g±199,69U/g). The conclusion of this study showed that the administration of alloxan significantly decreased pancreatic tissue catalase activity of rat and black cumin seed extract significantly increased catalase activity because cumin extract has antioxidant effects.